Kumar & Clark's cases in clinical medicine - Kumar, Parveen J. [ (Parveen June)]; Clark, Michael (Saunders/Elsevier, 2013)
Includes cases in Clinical Medicine that covers in handbook form with a range of acute medical conditions and problems that junior doctors are likely to encounter during the first years of training. This title is divided into chapters reflecting core medical specialties - including infectious diseases; STD; gastroenterology; and more